El raleo químico en floración incrementa el tamaño del fruto y el valor de la producción en durazno variedad Zee Lady - Osborne, Jason; Parra-Quezada, Rafael A.; Arreola-Ávila Jesús G. (Revista Mexicana de Ciencias Agrícolas, 2018)
In 2007, an experiment of flower and fruit thinning on peach was conducted in Nuevo Casas Grandes, Chihuahua, Mexico, in trees 5 years old, Zee Lady Variety, grafted onto the Bailey rootstock of seed. The variety ’Zee Lady’ is used for fresh consumption. The treatments were the control without applying; severe pruning at the time of full bloom, hand fruit thinning spaced approximately 15 cm, 45 days after full bloom, soybean oil (SO) 8% applied about 25 days before flowering, ammonium thiosulfate (ATS) (3.5%, 5%), lime sulfur (LS) (1%, 3%) plus soybean oil (SO) (2%) applied at 20% bloom, lime sulfur (LS) (1%, 3%) plus soybean oil (2%) applied at 90% bloom; wilthin (0.5%, 0.75%) applied at full bloom. The results indicate that the hand thinning reduces fruit set to 14%. ATS (5%), LS (3%) plus SO (2%) at full bloom, and severe pruning treatments were most effective in reducing the burden of fruit on the tree. LS (1%) plus SO (2%) to 20% bloom or full bloom, severe pruning, or soybean oil produces larger fruits. Wilthin (0.5%) was smaller than the control fruits. LS (1%) plus SO (2%) to 20% bloom or full bloom, severe pruning, or soybeanoil,ATS(3.5%),andWilthin(0.75%)generated the highest revenue in a range between 12 789.00 and 13 785.00 ha-1.